Concepção e implementação de um modelo de avaliação qualitativa para mapas conceituais estratificados em um estudo de caso no contexto de um curso de extensão sobre licitação na UFAL - Vieira, André Vilhena (2017)
Conceptual Maps (MCs) are used in various educational situations, such as meaningful learning resource and assessment tool. This dissertation proposes a qualitative evaluation model for conceptual maps of the evolution of meaningful learning, called the Stratified Conceptual Map (MCE), with facilities to attend in a particular way both the teacher and the student, using the information present in the map with attribution of the classes Optional, basic, mandatory and advanced concepts and characteristics of symmetry, transitivity and reflexivity relations. The objective is to increase the use of the traditional model by integrating the tasks of constructing and evaluating conceptual maps, facilitating the monitoring of the evolution of the student and / or the class, offering feedback to the student, with the possibility of self evaluation and helping the teacher In the evaluation of the evolution and quality of the mapped concepts. The research used a qualitative approach and its validation occurred during an extension course on Bidding at the Federal University of Alagoas (UFAL) with twelve participants. As data acquisition instruments, interview, questionnaire and brainstorming were used. The results show that the proposed model can help teachers in a qualitative evaluation of the maps of their students.